Are bloodstream leukocytes Trojan Horses for the metastasis of Staphylococcus aureus? - Thwaites, Guy E.; Gant, Vanya (Nature reviews. Microbiology, 2011)
Bacteraemia caused by Staphylococcus aureus infections can lead to life-threatening metastatic infections. Thwaites and Gant propose that neutrophils form a privileged site that is poorly accessible to antibiotics and that plays an important part in transporting the bacteria to distant sites. Staphylococcus aureus bacteraemia remains very difficult to treat, and a large proportion of cases result in potentially lethal metastatic infection. Unpredictable and persistent bacteraemia in the face of highly active, usually bactericidal antibiotics is the strongest predictor of death or disseminated disease. Although S. aureus has conventionally been considered an extracellular pathogen, much evidence demonstrates that it can survive intracellularly. In this Opinion article, we propose that phagocytes, and specifically neutrophils, represent a privileged site for S. aureus in the bloodstream, offering protection from most antibiotics and providing a mechanism by which the bacterium can travel to and infect distant sites. Furthermore, we suggest how this can be experimentally confirmed and how it may prompt a change in the current paradigm of S. aureus bacteraemia and identify better treatment options for improved clinical outcomes.